Open University in Postcovid-19 Periods. Collaborative Experience in Teacher Training: Case Study - Ortí-Martínez, José Antonio; González-Ortiz, Juan José; Burgueño-López, Jorge (Revista Electrónica Educare, 2023)
Introduction. This article presents the educational innovation project #educalabEDU and its subsequent results. Objective. This article (financed in an internal call by the Catholic University of Murcia) aims to develop 3.0 educational scenarios as a response to postCOVID-19 periods and link university teaching with professional practice in Early Childhood and Primary Education degrees at San Antonio Catholic University of Murcia and Comillas Pontifical University in Madrid. Methodology. This is an educational research project based on the results obtained from a questionnaire administered to 59 university students who participated in an educational innovation project. The project focuses on the educational use of the social network Twitter and collaborative learning among students. Direct contact with education professionals is encouraged through different sessions in the mentioned social network. Information is investigated and organized cooperatively. The project ends with developing an educational, social laboratory that puts future teachers in dialogue with experienced teachers. Results. The main results show high participation and motivation in the working methodology. The participating students say that the link between society and the university has been strengthened, promoting contact between students of different natures and origins. Conclusions. The conclusions show that a reciprocal communication space has been established, in which students and teachers with extensive professional experience have been able to share knowledge, reflections, and all kinds of didactic materials, resulting in a beneficial proposal for dialogical learning in the face of the pandemic.